A new species of the genus Phytoecia Dejean, 1835 (Coleoptera: Cerambycidae) from Greece - Szczepański, Wojciech T.; Karpiński, Lech (Zootaxa, 2017)
Phytoecia (Pilemia) kruszelnickii sp. nov. from Greece is described. Distinguishing characters from closely related species are given and discussed. Moreover, Phytoecia (Pilemia) moreana Breuning 1943 stat. nov. is distinguished as a separate species based on morphological and structural differences. According to the results of our research, P. kruszelnickii is distributed exclusively within the continental part of Greece (Thessaly region) and P. moreana only occurs in the Peloponnese peninsula. However, the taxonomic division and distribution range of Phytoecia (Pilemia) hirsutula (Frölich, 1793) require further research.